Vision-Based Feedback Control for High-Precision Beam Alignment using a Robotic Arm at ESS - Stjernfeldt,Timothy; Ulmestrand,Clara (2025)
This master thesis presents the development of a vision-based feedback control system for automating sample placement in a virtual neutron beam emulated using a laser. The thesis was carried out on behalf of the European Spallation Source (ESS) to investigate the feasibility, possibilities and limitations of using a robotic automation system for sample alignment. Due to the radioactive research environment at ESS, there is need for robotic sample handling to minimize risk for personnel as well as increase overall productivity. The system consists of a Stäubli TX60 robotic arm, two Basler CMOS cameras, a laser source simulating a neutron beam, and a sample prototype. An object detection model based on YOLO (You Only Look Once) was successfully trained to track the robot gripper, and an operating interface (OPI) was developed to monitor the system and integrate it with the control system used at ESS. The completed system is capable of automatically positioning the sample in the simulated beam and adjusting its orientation with the use of computer vision and algorithms that convert diffraction and backscatter patterns into movement commands for the robot. It reaches sub-millimeter positional repeatability and an orientational accuracy of approximately 0.1°. These results show that a vision-based robotic feedback system is a feasible and effective approach for automated sample alignment in research environments that demand high precision. The thesis has contributed to valuable insights into both the capabilities and limitations of such a system, laying a foundation for future development and integration into real ESS operations. To make this system usable in real experiments at ESS, future work will be needed to adapt the system to analyze neutron scattering patterns rather than the simplified diffraction and backscatter patterns used in this thesis.